Traffic-related Air Pollution and Pregnancy Loss. Issue 1 (January 2019) - Kioumourtzoglou, Marianthi-Anna; Raz, Raanan; Wilson, Ander; Fluss, Ronen; Nirel, Ronit; Broday, David M.; Yuval,; Hacker, Michele R.; McElrath, Thomas F.; Grotto, Itamar; Koutrakis, Petros; Weisskopf, Marc G.
Abstract : Background: Traffic-related air pollution has been linked to multiple adverse pregnancy outcomes. However, few studies have examined pregnancy loss, targeting losses identified by hospital records, a large limitation as it does not capture events not reported to the medical system. Methods: We used a novel variation of the time-series design to determine the association, and identify the critical window of vulnerability, between week-to-week traffic-related air pollution and conceptions resulting in live births, using nitrogen dioxide (NO2 ) as a traffic emissions tracer. We used information from all live births recorded at Beth Israel Deaconess Medical Center in Boston, MA (2000–2013) and all live births in Tel Aviv District, Israel (2010–2013). Results: In Boston (68, 969 live births), the strongest association was during the 15th week of gestation; for every 10 ppb of NO2 increase during that week, we observed a lower rate of live births (rate ratio [RR] = 0.87; 95% confidence interval [CI], 0.78, 0.97), using live birth–identified conceptions to infer pregnancy losses. In the Tel Aviv District (95, 053 live births), the strongest estimate was during the 16th gestational week gestation (RR = 0.82; 95% CI, 0.76, 0.90 per 10 ppb of NO2 ). Conclusions: Using weekly conceptions ending in live birth rather than identified pregnancy losses, we comprehensively analyzed the relationship between air pollution and all pregnancy loss throughout gestation. The observed results, with remarkable similarity in two independent locations, suggest that higher traffic-related air pollution levels are associated with pregnancy loss, with strongest estimates between the 10th and 20th gestational weeks. Abstract : Supplemental Digital Content is available in the text.